Seasonal variations of the sea level at Syowa Station,Antarctica - Nagata, Yutaka; Kawamiya, Michio; Michida, Yutaka; Odamaki, Minoru (National Institute of Polar Research, 1993)
P(論文) The sea level record at Syowa Station, Antarctica for the period from 1979 to 1988 is analyzed, and the seasonal variation of the sea level is investigated. The level reaches a maximum in early winter and falls to its minimum in mid-summer. The variation shape is very skewed with flat winter peak and sharp summer trough. The ascending speed of the sea-level in fall is much larger than the descending speed in spring. The correlation of the sea level change with several oceanographic and meteorological phenomena are discussed, and several possible mechanisms are reviewed. However, we cannot reach a definitive conclusion yet. departmental bulletin paper